Prevalence and outcomes of WPW pattern in the young: a report from a nationwide cardiac screening programme. (11th May 2022) - Maclachlan, H; Castelletti, S; Bhatia, R; Chatrath, N; Fyazz, S; Marwaha, S; Thurdnampetch, K; Gilchrist, J; Adil, S; Chang, V; Basu, J; Miles, C; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Individuals with accessory pathways, also referred as the Wolff-Parkinson-White pattern (WPWp), are usually asymptomatic and fatal arrhythmias may be the first presentation. Risk stratification is recommended, with electrophysiological study (EPS) being the gold standard. Catheter ablation offers a widely available, curative option, and provides incentive for screening, particularly in high-risk populations such as athletes. Purpose: We sought to assess the prevalence, real-world clinical practice and outcomes of WPWp in young individuals identified through a nationwide cardiac screening programme. Method: Between 2008 and 2018, 113, 209 consecutive individuals (14 to 35 years old, 38% female) underwent cardiac screening with a health questionnaire, 12-lead electrocardiogram (ECG) and cardiology consultation. Individuals with suspected cardiac disease were referred for further investigations as necessary. Clinical outcomes were obtained via an online questionnaire and matched de-identified records from the Office of National Statistics database. Individuals were classified as elite athletes, non-elite athletes and non-athletes. Results: A total of 214 (0.2%) individuals were referred for secondary evaluation with a suspected WPWp (Figure 1). Clinical outcomes were unavailable for 30 (14%) individuals. Follow-up confirmed an additional 13 individuals with a WPWp who were deemed to have normal investigations at screening, of which 8 (61%) had reported cardiovascular symptoms on their HQ and, in retrospect, 4 (30%) demonstrated subtle WPWp on their ECG. A WPWp was confirmed in 187 individuals (0.2%), of which 149 (80%) individuals were considered non-athletes, 114 (61%) reported cardiovascular symptoms, 116 (62%) underwent risk stratification with an EPS and 95 (43%) underwent catheter ablation. Report of palpitation was significantly greater in non-athletes than athletes (p=0.034). In asymptomatic individuals, those engaging in sports at elite level were more likely to be referred for an EPS (p=0.04). Four adverse cardiac events were reported over a follow up period of 7.4 years (IQR 4.9 to 9.2), including 3 individuals (16 years, 20 years, 40 years) with life-threatening arrhythmic events (LAE) requiring cardioversion, and 1 individual (20 years) with sudden cardiac death. Of these 4 individuals, only 1 with a LAE had undergone risk stratification with EPS. Conclusions: The incidence of SCD in this young screened population was 0.72 per 1000 person-years. Clinical practice was variable and EPS was not offered to a significant proportion of patients, despite inadequate non-invasive risk stratification. The indication to EPS was driven by the athletic status in the asymptomatic individuals. The WPW syndrome may manifest with subtle ECG changes, posing a diagnostic challenge to interpreting physicians.